Using Kahoot! To Improve Skimming and Scanning Skills - Mala, Jamilatul; Mustofa, Mutmainnah; Jihad, Muhammad Syaiful; Hariyanto, Sugeng (EDUTEC : Journal of Education And Technology, 2023)
There are a variety of technology instruments and software that can be utilized to improve language teaching and learning. According to research, integrating 'gamification' based software like Kahoot! into language, schools can affect and improve language learning results and can be utilized as effective teaching and assessment tools. This study examines the language learning experiences of eleven junior high school students in an international class that used Kahoot! in their English classes, focusing on skimming and scanning. According to the findings of the study, almost all of the students reported favorable outcomes when Kahoot! was used in their courses. The majority of students said that using Kahoot! in their English classes helped them improve their skimming and scanning skills. In general, it was discovered that using the skimming and scanning reading techniques, Kahoot! enabled students to have a better understanding of the content.